The effects of knowledge management on innovative success: an empirical analysis of German firms - Uwe Cantner; Kristin Joel; Tobias Schmidt (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
The aim of this paper is to analyse the effects of knowledge management on the innovation success of firms in Germany. Using a matching procedure on data from the German Innovation Survey of 2003 (“Mannheim Innovation Panel”), we pair firms applying knowledge management with twin firms with similar characteristics not applying knowledge management. Our focus is on investigating the effects of knowledge management techniques on the economic success of firms with product and process innovations. The results of our matching analysis reveal that firms which apply knowledge management perform better in terms of higher-than-average shares of turnover with innovative products compared to their twins. We do not find a significant effect of knowledge management on the share of cost reductions with process innovation.
Keywords: O32; L23; L25; M11; 330; knowledge management; innovation; matching estimator; Wissensmanagement; Innovation; Erfolgsfaktor; Schätzung; Deutschland